Performance of Water Utilities in Africa - van den Berg, Caroline; Danilenko, Alexander (World Bank, Washington, DC, 2017)
Africa’s urban population is growing rapidly. Between 2000 and 2015, the urban population increased by more than 80 percent from 206 million to 373 million people. Although access to piped water increased over the period (from 82 million urban dwellers with piped water in 2000 to 124 million in 2015), African utilities were not able to keep up with the rapid urbanization as reflected in the decline of piped water as a primary source of water supply in percentage terms. The objective of this assessment is to inform Bank and government policies and projects on the drivers of utility performance. The report describes the main outcomes and lessons learned from the assessment that identified and analyzed the main features of water utility performance in Africa. The report includes the following chapters: chapter one gives introduction, chapter two describes the methodology used in the study, including details on the data collection process. In chapter three, the study team undertook a trend analysis of utility performance of the sector. Chapter four examines the efficiency of utilities using a data envelopment analysis (DEA) while also using an absolute performance approach. Chapter five investigates the effect of institutional factors on utility performance. Chapter six presents an econometric analysis of the drivers of utility performance, using various definitions of utility performance. The results from the econometric models are triangulated with a set of case studies of five utilities (Burkina Faso’s l’Office National de l’Eau et de l’Assainissement (ONEA), Cote d’Ivoire’s la société de distribution d’eau de la Côte d’Ivoire (SODECI), Kenya’s Nairobi City Water and Sewerage Company (NCWSC), Senegal’s Sénégalaise des Eaux (SDE), and Uganda’s National Water and Sewerage Corporation (NWSC), similar to those that the electricity study team undertook, which are presented in chapter seven. The report concludes in chapter eight with the lessons learned from the assessment.